Effects of Prophylactic Administration of Granulocyte Colony-Stimulating Factor on Peripheral Leukocyte and Neutrophil Counts Levels After Chemotherapy in Patients With Early-Stage Breast Cancer: A Retrospective Cohort Study - Tian, Wei; Wang, Yali; Zhou, Yunxiang; Yao, Yihan; Deng, Yongchuan (Frontiers in Oncology, 2022)
Chemotherapy-induced neutropenia(CIN) and febrile neutropenia(FN) are both frequent chemotherapy dose limit toxicity.Primary prophylactical use of recombinant human granulocyte colony stimulating factor significantly reduces the risks of CIN and FN during chemotherapy in patients with early-stage breast cancer.We investigated the variation tendency and recovery of WBC and ANC during and after chemotherapy, evaluated independent influencing factors of leukopenia and neutropenia lasting longer after chemotherapy. We aim to provide individualized prophylactically leukocyte elevation therapy for breast cancer patients.